THE INFLUENCES OF ECCENTRIC FORCES ON THE TIBIA BONE WHILE STANDING IN THE FLAT FOOT CASE - Ачхарджит, Пармар; Юнис, Башир (SWorldJournal, 2021)
The most important fact is that the intensified stress on the tibia bone which is caused by the eccentric force which induces the foot to flatten, can lead to fractures. However, the value of this stresses is conditional on the concentrated load with the